Direito à literatura e formação dos mediadores: relato de experiência - Stringhetta, Karoline de Souza [UNESP]; Souza, Renata Junqueira de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The mediator's role in literature is to make the text of an object to be explored, analyzed and even deconstructed if necessary for understanding of one who reads it. Anyone can be a mediator of reading, not only the teacher and can be mediation at any age, no age restriction. Thus, the work of mediators within the Center for Children's Reading and Youth (CELLIJ) is to get the reader to take ownership of what is being read, to exercise autonomously this practice through the moments of storytelling that take place in the "Story Time". Mediation in this sense is an act to make the words, texts circulating in society, short stories, novels, poems, become part of the life experience of the student. Moreover, because we seek to form a reading mediator? Therefore, there is the democratization of reading, so this strikes mostly those who have less access to literature books. In this sense, besides allowing the right to literature that children have the CELLIJ also contributes to the training of mediators to develop study groups and research with graduate students of Unesp - object of study of this text.

O papel do mediador na literatura é fazer do texto um objeto a ser explorado, analisado e até desconstruído, se necessário para compreensão daquele que o lê. Qualquer pessoa pode ser um mediador de leitura, não só o professor e também pode haver a mediação em qualquer idade, sem restrição de faixa etária. Sendo assim, o trabalho dos mediadores dentro do Centro de Estudos em Leitura Infantil e Juvenil (CELLIJ) é fazer com que o leitor se aproprie do que está sendo lido, para que exerça de forma autônoma essa prática através dos momentos de contação de histórias que acontecem na “Hora do Conto”. A mediação, nesse sentido, é um ato de fazer com que as palavras, os textos circulantes na sociedade, os contos, os romances, os poemas, passem a fazer parte da experiência de vida do aluno. E porque buscamos formar um mediador de leitura? Para que haja a democratização da leitura, para que essa atinja principalmente aqueles que menos têm acesso aos livros de literatura. Neste sentido, além de possibilitar o direito à literatura que as crianças têm, o CELLIJ também colabora na formação de mediadores ao desenvolver grupos de estudo e de pesquisa com os graduandos da Unesp – objeto de estudo deste texto.
Keywords: Reading; Literature; Mediation; Leitura; Literatura; Mediação